BANDURA’S LEARNING THEORIES: TEACHING PRONUNCIATION FOR TEACHERS IN KINDERGARTEN - Ayu Bandu Retnomurti (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2017)
There are so many to be found inappropriate to pronounce the English vocabularies for students in all education level in Indonesia. Therefore, it needs appropriate pronunciation practice for kindergarten teachers, by using modelling method from Bandura’s theory, to be learned for students in the beginning which is when they are in Kindegarten. This research is important to be carried out because the level of making characters by them in teaching learning process starts from kindergarten era. In here, the source of the data from TK Sekar Ananda Depok. The research finding is based on taking sample in practicing teachers one by one, the total of teachers in TK Sekar Ananda is 10 teachers, but 8 teachers who did not yet pronounce well and 2 teachers who have pronounced well. From the data, it can be showed that the amount of sample in pronounce the vocabularies for teachers which is who did not yet pronunciation well is many more than the sample who have pronounced well, that is because inappropriate to pronounce the English vocabularies for students in Kindergarten. Here are some of the main in modelling method from students who taught by their teachers in TK Sekar Ananda Depok such as Attention, Retention, Reproduction, and Motivation. By using modelling method from Bandura’s theory, to pronounce the English vocabulary, the English teacher has to introduce the features of pronunciation like consonant sounds and vowel sounds to their students in order to increase the ability to pronounce the vocabulary well. Keywords: Pronunciation, vocabulary, modelling method, Bandura’s theory